Effect of Financial Performance on Economic Growth (district/city case study on Sumatera Island) - Mohammad Benny Alexandri (Universitas Dharma Wacana, 2022)
Study this aim for knowing role Performance Finance Area on the Economic Growth of Regency/City in Sumatra Island. Data The research is secondary data in the form of Local Government Budget Realization Reports and 2010 Series GRDP Growth Rate based on Regency/City Expenditure in Sumatra island Year 2017-2021. Population in study this totaling 10 regencies/cities on the island of Sumatra, with the determination of the sample ie saturated sample. Data were analyzed by multiple linear regression analysis. Analysis results indicates Ratio independence (RK), Ratio Effectiveness (RE), and Ratio Growth (RP) is rejected which means that RK, RE, and RP do not significantly affect significant to Growth Economy area in Sumatra island. Whereas RE received which means RE influence significant to Growth Economy area in Sumatra island. Thing the indicates the level of financing in order to obtain income with realization income already efficient. Besides that, RK, RE, and RP by together influence Growth Economy area in Sumatra island